The New Search for E.T. - Ross, M. (IEEE spectrum)
A new telescope has been especially designed and constructed at the Oak Ridge Observatory to detect pulses of visible light that a far-off civilization could be sending toward Earth. Unlike a regular imaging telescope, the new telescope has no lens, nor is it designed to pluck pristine images of celestial bodies orbiting overhead. It uses a 1.8 m diameter mirror and a 0.9 m secondary mirror to scoop up raw photons from the sky. Called photon buckets, they are less expensive to build and operate than imaging telescopes. A key feature is its use of multipixel photomultiplier tubes that allows more star systems to be observed at a time